Carbaborane-based alkynylphosphanes and phospholes. Issue 5 (20th November 2014) - Kreienbrink, Anika; Sárosi, Menyhárt B.; Kuhnert, Robert; Wonneberger, Peter; Arkhypchuk, Anna I.; Lönnecke, Peter; Ott, Sascha; Hey-Hawkins, Evamarie
Abstract : 1, 2-Bis( N, N -dimethyl-aminochlorophosphanyl)-1, 2-dicarba- closo -dodecaborane(12) reacts with lithiated phenylacetylene to give a carbaboranyl-based phosphane, while alkynylchlorophosphanes and dilithiated carbaborane give bis(alkynylphosphanyl)carbaboranes. Abstract : The reaction of 1, 2-bis( N, N -dimethylaminochloro-phosphanyl)-1, 2-dicarba- closo -dodecaborane(12) and lithiated phenylacetylene gives a five-membered dihydrophosphole derivative with an exocyclic phosphanyl group. This unexpected reaction opens new possibilities for the synthesis of carbaborane-containing phosphorus heterocycles. P, P ′-alkynylated 1, 2-bis(phosphanyl)-1, 2-dicarba- closo -dodecaborane(12)s are obtained from alkynylchlorophosphanes and dilithiated carbaborane. This new class of alkynes can be used for future applications in cyclizations and polymerizations.